Diffusion and molecular interactions in a methanol/polyimide system probed by coupling time-resolved FTIR spectroscopy with gravimetric measurements - Musto, Pellegrino; Galizia, Michele; La Manna, Pietro; Pannico, Marianna; Mensitieri, Giuseppe (Frontiers in Chemistry, 2014)
In this contribution the diffusion of methanol in a commercial polyimides (PMDA-ODA) is studied by coupling gravimetric measurements with in-situ, time-resolved FTIR spectroscopy. The spectroscopic data have been treated with two complementary techniques, i.e. difference spectroscopy (DS) and least-squares curve fitting (LSCF). These approaches provided information about the overall diffusivity, the nature of the molecular interactions among the system components and the dynamics of the various molecular species. Additional spectroscopic measurements on thin film samples (about 2 μm) allowed us to identify the interaction site on the polymer backbone and to propose likely structures for the H-bonding aggregates. Molar absorptivity values from a previous literature report allowed us to estimate the population of first-shell and second-shell layers of methanol in the polymer matrix. In terms of diffusion kinetics, the gravimetric and spectroscopic estimates of the diffusion coefficients were found to be in good agreement with each other and with previous literature reports. A Fickian behaviour was observed throughout, with diffusivity values markedly affected by the total concentration of sorbed methanol.